If health organisations and staff engage in research, does healthcare improve? Strengthening the evidence base through systematic reviews - Annette Boaz; Belinda Goodenough; Stephen Hanney; Bryony Soper (BMC, 2024)
Abstract Background There is an often-held assumption that the engagement of clinicians and healthcare organizations in research improves healthcare performance at various levels. Previous reviews found up to 28 studies suggesting a positive association between the engagement of individuals and healthcare organizations in research and improvements in healthcare performance. The current study sought to provide an update. Methods We updated our existing published systematic review by again addressing the question: Does research engagement (by clinicians and organizations) improve healthcare performance? The search covered the period 1 January 2012 to March 2024, in two phases. First, the formal updated search ran from 1 January 2012 to 31 May 2020, in any healthcare setting or country and focussed on English language publications. In this phase two searches identified 66 901 records. Later, a further check of key journals and citations to identified papers ran from May 2020 to March 2024. In total, 168 papers progressed to full-text appraisal; 62 were identified for inclusion in the update. Then we combined papers from our original and updated reviews. Results In the combined review, the literature is dominated by papers from the United States (50/95) and mostly drawn from the Global North. Papers cover various clinical fields, with more on cancer than any other field; 86 of the 95 papers report positive results, of which 70 are purely positive and 16 positive/mixed, meaning there are some negative elements (i.e. aspects where there is a lack of healthcare improvement) in their findings. Conclusions The updated review collates a substantial pool of studies, especially when combined with our original review, which are largely positive in terms of the impact of research engagement on processes of care and patient outcomes. Of the potential engagement mechanisms, the review highlights the important role played by research networks. The review also identifies various papers which consider how far there is a "dose effect" from differing amounts of research engagement. Additional lessons come from analyses of equity issues and negative papers. This review provides further evidence of contributions played by systems level research investments such as research networks on processes of care and patient outcomes.